Waste to wealth : Low cost fruiting body substrate for pleurotus ostreatus cultivation using various agro-industrial wastes in Malaysia: application of natural calcium source - Fathie, Ahmad Zakil; Khai Qi, Low; Norfaznila, Mohammad; Nur Adila Aida, Salahutheen; Khaled Nasser, Aldafri (2021)
Massive amount of oil palm factory in Malaysia represent the amount biomass waste is in large quantity too. This lignocellulosic agricultural waste (AW) has a potential to be the alternative media that can replace rubber tree sawdust (RS) to become the growing media for the production of Pluerotus Ostreatus. Nutrients in this biomass waste is not enough for the growth of mushroom. Therefore, eggshells (ES) will be added into the substrate as calcium source. Demand of mushroom is high as Figure 1 shows the increasing quantity of mushroom that Malaysia import from other countries in order to overcome the high demand.